Pengaruh Pijat Bayi terhadap Durasi Menyusu Pada bayi di PMB Sri KD Lahat 2024 - Nia Clarasari Mahalia Putri; Nurayuda N; Jenny Kartika (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The duration of breastfeeding varies according to the baby’s suction pattern. If breastfeeding takes too long (more than half an hour) or too short (less than 4 minutes), this indicates a possible problem with the attachment between the baby and the mother’s nipple. The suckling frequency of the baby will greatly affect the baby’s physical and emotional frequency with the duration and the duration of the feed will improve the baby’s calm condition and the baby’s weight will increase. Attempts to offer improved calm conditions and baby weight one of them is baby massage on the duration of breastfeeding in infants. The research design is quasi-experiment with non-equivalent control group design. This sampling by purposive sampling technique. Sample size 30 groups a large sample in the intervention group of 15 people and a control group of 15 people. Based on the results of univariate analysis before the massage and did not do the baby massage most of the duration of short suckling amounted to 23 respondents (70%), afterbeing given infant massage treatment and not done infant massage most babies have long duration of feed that is amounted to 16 respondents (53.3%) can be known some babie suckle after the massage amounted to 15 respondents (50%) ie 14 respondents (46.7%) following the length. And some infants suckled after no long-term breastfeeding 2 (6.7%) breast-feeder massage. From the result of bivariate test analysis using test of Wilcoxon Sign Rank Test, got significant value that is (p value: 0.000), so p